Design of new infrared nano sensor based on surface plasmon resonance photonic crystal fibers. (1st October 2022) - Moayed, Seyed Hossein; Sadeghi, Mojtaba; Adelpour, Zahra
Abstract: In this paper, five different surface plasmon resonance photonic crystal fiber (SPR-PCF) structures are proposed and evaluated by numerical modeling. The structures are based on photonic crystal fibers with defects rods of air, Au, and TiN in the background of silica. In the fourth and fifth designs, two grooves coated with gold layers are considered to improve the functionality of the structures and help the analyte to become closer to the fiber core. The effects of geometrical parameters like radius, thickness, and width on the loss spectrum are also investigated, and the results are presented. Finally, a double D-shaped SPR-PCF sensor with ITO belts and U-shaped grooves covered with gold is proposed. The proposed sensor can detect a low RI change from 1.4 to 1.6 with a maximal sensitivity factor around 6000 (nm/RIU). The proposed SPR-PCF sensor can be an appropriate candidate in nano-optical integrated circuits (for different applications) due to its compact size and high sensitivity factor.